Fixed-Term Employment and Fertility: Evidence from German Micro Data - Wolfgang Auer; Natalia Danzer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
We study the short- to medium-run effects of starting a career on a fixed-term contracton subsequent fertility outcomes. We focus on the career start since we expect thattemporary contracts and their inherent economic uncertainty implies a path dependencywhich might have spill-over effects on other domains of life. Our empirical analysis isbased on rich data from the German Socio-Economic Panel which provides comprehensiveinformation about individuals labour market history as well as fertility behavior. Ourmain results are: Women (i) tend to postpone first birth due to fixed-term employmentat labour market entry and (ii) reduce the number of children in the first 10 years aftergraduation. These associations are strongest in the subsample of native women with atleast vocational training. (iii) In contrast, we find no significant correlations for men.We argue that these findings are robust to potential endogeneity threats.
Keywords: J13; J18; J41; 330; Career start; fixed-term employment; postponement of maternity; fertility; economic uncertainty